Analisis Framing Pemberitaan Status Keanggotaan Palestina di Perserikatan Bangsa-Bangsa pada CNNIndonesia.com - Rifaldo, Alfan; Choiriyati, Sri; Meiranti, Mike (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The media plays an essential role in shaping public opinion on complex global issues, including Palestine’s efforts to obtain full membership in the United Nations (UN). CNNIndonesia.com, as one of Indonesia’s national news portals, reported on this matter through several articles published between April 18 and May 18, 2024. This study aims to analyze CNNIndonesia.com’s framing of news coverage regarding Palestine’s UN membership status using Robert N. Entman’s framing analysis model. The research employed a descriptive qualitative method with text analysis of three CNNIndonesia.com news articles. The findings reveal that CNNIndonesia.com’s framing highlights formal diplomacy and the dominance of major power narratives, while direct representation from Palestine is relatively limited. The coverage also relies more on external sources and international actors than on Palestinian voices or supporting organizations, thereby creating a narrative that is not fully balanced. In addition, Indonesia’s foreign policy context provides a background to how the Palestinian issue is constructed by the media. The conclusion of this study is that CNNIndonesia.com’s framing tends to emphasize political and diplomatic aspects, which consequently limits the public’s ability to fully understand the substance of Palestine’s UN membership, while also underscoring the importance of media literacy.